Evolutionary and Structural Perspectives of Plant Cyclic Nucleotide-Gated Cation Channels - Zelman, Alice K.; Dawe, Adam; Berkowitz, Gerald A.; Gehring, Christoph (Frontiers in Plant Science, 2012)
Ligand-gated cation channels are a frequent component of signaling cascades in eukaryotes. Eukaryotes contain numerous diverse gene families encoding ion channels, some of which are shared and some of which are unique to particular kingdoms. Among the many different types are cyclic nucleotide-gated channels (CNGCs). CNGCs are cation channels with varying degrees of ion conduction selectivity. They are implicated in numerous signaling pathways and permit diffusion of divalent and monovalent cations, including Ca2+ and K+. CNGCs are present in both plant and animal cells, typically in the plasma membrane; recent studies have also documented their presence in prokaryotes. All eukaryote CNGC polypeptides have a cyclic nucleotide-binding domain and a calmodulin binding domain as well as a six transmembrane/one pore tertiary structure. This review summarizes existing knowledge about the functional domains present in these cation-conducting channels, and considers the evidence indicating that plant and animal CNGCs evolved separately. Additionally, an amino acid motif that is only found in the phosphate binding cassette and hinge regions of plant CNGCs, and is present in all experimentally confirmed CNGCs but no other channels was identified. This CNGC-specific amino acid motif provides an additional diagnostic tool to identify plant CNGCs, and can increase confidence in the annotation of open reading frames in newly sequenced genomes as putative CNGCs. Conversely, the absence of the motif in some plant sequences currently identified as probable CNGCs may suggest that they are misannotated or protein fragments.